Isolasi dan karakterisasi cendawan endofit asal rizosfer bawang merah “Lembah Palu” dan potensinya menghambat penyakit bercak ungu Alternaria porri (ELL) CIF - Sri Sudewi; Ratnawati Ratnawati; Kasman Jaya; Sitti Hardiyanti (Jurusan Agroteknologi, 2023)
The decrease in shallot production due to Alternaria porri infection can reach 50%-70% or can even cause crop failure. One of the biological control methods to overcome this is by utilizing antagonistic microbes. The purpose of this study was to identify endophytic fungi from the rhizosphere of shallots